Reduced coagulation at high altitude identified by thromboelastography - Martin, Daniel S.; Pate, Jim S.; Vercueil, Andre; Doyle, Patrick W.; Mythen, Michael G.; Grocott, Mike P. W.; for the Caudwell Xtreme Everest Research Group (Thrombosis and Haemostasis, 2012)
The impact of hypoxaemia on blood coagulation remains unclear despite use of a variety of measures to address the issue. We report the first use of thromboelastography (TEG) at high altitude to describe the dynamics of clot formation in whole blood samples. Seventeen healthy volunteers ascended to 5,300 m following an identical ascent profile; TEG measurements at 4,250 m and 5,300 m were compared with those from sea level. Peripheral oxygen saturation (SpO2) and haematocrit were also measured. Ascent resulted in a decline in SpO2 from 97.8 (± 1.2) % at sea level to 86.9 (± 3.3) % at 4,250 m and 79.5 (± 5.8) % at 5,300 m (p<0.001); haematocrit rose from 43.7 (± 2.8) % at sea level, to 46.7 (± 3.9) % and 52.6 (± 3.2) % at 4,250 m and 5,300 m, respectively (p<0.01). TEG reaction (R)-time and kinetic (K)-time were both increased at 5,300 m compared to sea level, 8.95 (± 1.37) minutes (min) to 11.69 (± 2.91) min (p=0.016) and 2.40 (± 0.66) min to 4.99 (± 1.67) min (p<0.001), respectively. Additionally the alpha (α)- angle was decreased from 57.7 (± 8.2) to 51.6 (± 6.4) (p<0.001). There was no change in maximum amplitude (MA) on ascent to altitude. These changes are consistent with an overall pattern of slowed coagulation at high altitude.
Keywords: Altitude; hypoxia; blood coagulation; thrombelastography; blood coagulation tests